Implementation of Entity Financial Accounting Standards Without Public Accountability (SAK-ETAP) for Freshwater Lobster Cultivating SMEs in Tanjung Morawa District - Andri Irawan; Laylan Syafina; Yenni Samri Juliati Nasution (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Accounting standards for financial entities without public accountability (SAK-ETAP) Facilitate MSMEs in preparing financial reports. This study analyzes MSME actors in recording financial reports based on SAK-ETAP. The method in this study uses a qualitative method and the method of analysis used is descriptive. The sample in this study is the perpetrators of SMEs in freshwater lobster cultivation in the Tanjung Morawa sub-district. The results of the study show that the recording and preparation of financial reports carried out by the MSME managers of Freshwater Lobster Cultivation in Tanjung Morawa District are not in accordance with SAK-ETAP. It is suggested to the DSAK (Financial Accounting Standards Board) that there is a need for supervision that functions to supervise and evaluate the implementation of SAK-ETAP for MSME actors to make it easier for business actors to organize and plan their business according to SAK-ETAP principles and Islamically according to the rules of Al-Qur’an Surah Al-Baqarah verse 282.